1988
DOI: 10.1002/ajh.2830270103
|View full text |Cite
|
Sign up to set email alerts
|

Cause of death in hemophilia a patients in the United States from 1968 to 1979

Abstract: Death data on 949 hemophiliacs for the years 1968-1979 have been analyzed. The median age at death has increased from 33 to 55 years. There was no evidence of new diseases caused by the more intensive therapy during this time interval. The leading infectious disease was hepatitis, accounting for eight deaths. Only one acute hepatitis death was listed after 1974, when sensitive tests for hepatitis B antigen screening of plasma were implemented. Cirrhosis was a primary or associated cause of death in 76 cases (8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 25 publications
2
50
1
Order By: Relevance
“…The most common cause of death in hemophilia still is hemorrhage, although it no longer constitutes the sole death cause: in our study it accounted for half of the deaths [78,93,102,112,129,148]. In a recent report on almost a thousand deaths of hemophilia patients in the USA from 1968 to 1979, it was observed that the ratio of the number of deaths by ischemic heart disease over the number of cancer deaths was much smaller than in the general population [7]. It was not possible from this study to conclude whether this was caused by an increased mortality from cancer or a decreased mortality from ischemic heart disease, since this was not a follow-up study: the number of deaths could only be compared relative to each other [proportional mortality ratios (PMR)].…”
Section: Mortality and Life Expectancymentioning
confidence: 53%
See 1 more Smart Citation
“…The most common cause of death in hemophilia still is hemorrhage, although it no longer constitutes the sole death cause: in our study it accounted for half of the deaths [78,93,102,112,129,148]. In a recent report on almost a thousand deaths of hemophilia patients in the USA from 1968 to 1979, it was observed that the ratio of the number of deaths by ischemic heart disease over the number of cancer deaths was much smaller than in the general population [7]. It was not possible from this study to conclude whether this was caused by an increased mortality from cancer or a decreased mortality from ischemic heart disease, since this was not a follow-up study: the number of deaths could only be compared relative to each other [proportional mortality ratios (PMR)].…”
Section: Mortality and Life Expectancymentioning
confidence: 53%
“…Evidence of cirrhosis has been reported in 15-38% of hemophilia patients [4,57]. In the USA liver disease accounted for 9% of the deaths in hemophilia patients between 1968 and 1979 [7]; surprisingly, in our more recent study of mortality over the period 1973 -1986 no deaths from liver disease were noted [112].…”
Section: Transfusion-transmitted Diseasementioning
confidence: 84%
“…[16][17][18] There were noticeable numbers of the fatal spontaneous CNS bleeding events in the surveyed patients with hemophilia. This may be due to limited access to the coagulation factor concentrates in their country in the past decades.…”
Section: Discussionmentioning
confidence: 99%
“…In the 1960s and 1970s, the introduction of factor replacement therapy, the development of comprehensive hemophilia treatment centers, and the implementation of home care for this population decreased the number and proportion of deaths due to hemorrhage [7], dramatically increasing their median age at death [33,34]. In this study, these perturbations are underscored by the disparity in the median age at death in 1995-1998 for persons with hemophilia A between those with HIV-related disease (33 years) and those without HIV-related disease (72 years).…”
Section: Continuing Importance Of Hemorrhagic Phenomenamentioning
confidence: 99%